Integrated STEM-Problem Based learning Model: Its Effect on Students' Critical Thinking - Nurazmi Nurazmi; Hartono Bancong (Kasuari: Physics Education Journal (KPEJ), 2021)
This study aims to find out: 1) the level of students' critical thinking skills in solving physics problems after implementing the integrated STEM-Problem-based Learning model, 2) the level of students' critical thinking skills in solving physics problems after implementing conventional learning model, and 3) the difference between students' critical thinking skills in solving physics problems when taught by using the integrated STEM-PBL model and the conventional learning model. Being a true experimental research with Pretest-Posttest Control Group Design, this research involved the students of class X MIA 1 and X MIA 2 at SMAN 4 Takalar, consisting of 35 students each. A test of critical thinking skills was used to collect the data needed. Based on the results of analysis, it can be concluded that most of the students’ scores in the experimental class taught by using the integrated STEM-problem-based learning model are in the high category (71.43%), while the rest (28.57%) performed very high category scores. In the control class, taught by using conventional learning, almost all the students’ scores (82.86%) are in medium category, and the rest (17.14%) scored high. Therefore, it can be concluded that there is a significant difference between the critical thinking skills of students who were taught using the integrated STEM-PBL model and the conventional learning model.